Development of Organizational and Methodological Support of Accounting at Small Enterprises - S. N. Polenova (Учёт. Анализ. Аудит, 2019)
The important role small enterprises play in economy acts as a motivator for the work on substantiating the directions of their development, organization and methodological support of national accounting. The purpose of the article is to provide recommendations on improvement of organization and methodology of accounting at small enterprises taking into consideration their importance and peculiarities of their activity. The methodological base for the research is the practice of accounting, regulations and legislative documents, results of scientific research made by the authors, general scientific methods: comparison, comparison, deduction, induction, analysis, syntheses, generalization and grouping. As a result there were identified the following problems: insufficient qualification of accountants employed by small businesses and lack of opportunities for their professional growth. The article justifies the need to develop the chart of accounts for small enterprises which apply the simplified accounting and an instruction on how to use this chart and federal standards of accounting “Accounting at small business enterprises” and “Accounting (financial) reports at small business enterprises”. The results of the research can be used in the theory and practice of accounting at small businesses to substantiate the directions of its development.